Improvement High School Students' Science Literacy through the Implementation of Blended Learning with SETS Vision - Puspitasari, Devi; Indriyanti, Dyah Rini; Haryani, Sri (Journal of Innovative Science Education, 2022)
Blended learning is a learning model that combines face-to-face and online learning activities, so that in its implementation it can be combined with an appropriate approach, namely SETS as an effort to improve students' science literacy. This study aims to find out the improvement of students' science literacy by applying blended learning with SETS vision on environmental change learning materials. The research was conducted with quasi-experimental method with randomized pretest - posttest control group design. The subject of this research was all students of X MIPA at SMA Negeri 1 Gabus, with cluster random sampling technique, X MIPA 1 was obtained as the control group and X MIPA 3 as the experiment group. The results of the research was proven by statistical test analysis, specifically used the independent sample t-test, it showed a result of 3.10, The analysis figured out that there was a significant difference between the application of blended learning with SETS vision and conventional blended learning on increasing students' science literacy on lesson of environmental change. The results of this research can be conclude that the application of blended learning with SETS vision significantly increased students’ science literacy meanwhile compared to the implementation of the learning model in the control group through conventional blended learning.